Report of the agricultural sample survey in Oyo state - Ministry of economic planning; Oyo state; Oyo state (Ibadan Oyo State Government, 1983)
This report include all the agricultural produce of Oyo state. The survey examine the estimates of various produce including animals, crops and extension services to ascertain the economic importance in terms of GDP growth for state.
Includes estimates of cattle, sheep, goats, draught animals (horses, mules, asses, and camels), poultry, and beehives.
asm; 06./03/19
Loans
Keywords: Livestock; Poultry; Beehives; Agricultural surveys; Agricultural surveys; Beehives; Livestock; Poultry; Oyo state